Strategi Komunikasi Pondok Pesantren Nurul Iman Desa Ujung Tanjung Dalam Menanamkan Nilai-Nilai Akhlak Kepada Santri - rati hafsa sari; Aliasan Aliasan; Ahmad Harun Yahya (Program Studi Jurnalistik, Universitas Islam Negeri Raden Fatah Palembang, 2023)
ABSTRACT Islamic boarding schools have a significant role in religious education institutions whose existence is continuously needed to foster adjustments or improvements in behavior in Tazkiyatun Nafs (purification of the heart) and self-approach to Allah SWT. The purpose of this study was to find out how the interaction of Islamic boarding schools with students in developing their values at the Nurul Iman Islamic boarding school, Ujung Tanjung Village. This study was conducted to clarify the communication plan for the Nurul Iman Islamic Boarding School in Ujung Tanjung Village. Because it is a religious organization that offers education, the authors choose the Nurul Iman Islamic Boarding School. Having a vision, mission, and goals as an Islamic educational institution engaged in education, and to achieve these goals the Nurul Iman Islamic Boarding School uses an effective communication strategy, therefore a thesis written by the author entitled